Digital landscape assessment for climate services : Asian Mega Deltas - Giles, James; Bich, Ngoc Vu Thi; Khanam, Fahmida; Khaung, Ye; Soksophors, Yim; Le, Thi Tam; Phanna, Khieng; Chou, Phanith; Bora, Chan Borey; Phyu, Thant; Amjath-Babu, Tharayil Shereef; Swaans, Cornelis (2023)
This study was conducted through the CGIAR Asian Mega -Deltas (AMD) initiative, a multi -year research program to secure food systems of the Mekong Delta, Irrawaddy Delta, and the Ganges Delta for climate and livelihood resilience. The study contributes to Work Package 3 (WP 3) on derisking delta orientated value chains through bundled digital climate advisory services (DCAS+), and focuses on Vietnam, Cambodia, Myanmar, and Bangladesh. DCAS comprise mobile phones, digital platforms, radio, and TV, as well as digitally enabled services such as extension services and printed bulletins. This suite of technologies offers targeted climate information and advisories to farmers, helping them adapt to climate variability (Kumar, 2021). Meanwhile, DCAS+ include complementary services bundled with DCAS to increase engagement from potential users and generate supplementary revenue streams for sustaining the service. DCAS+ also aid in eliminating barriers, including financial constraints and challenges related to accessing inputs, that impede farmers from implementing recommended practices (Tsan et al., 2019; WBCSD, 2021). The main objective of this study was to map out the DCAS+ landscape in each of the target deltas. Specifically, the study described: 1) the types of tools that are currently available; 2) the information and advisories provided; 3) the target audiences of information products; 4) the means by which these audiences are reached; and 5) the types of business models applied, if any. This was achieved through a combination of desk research, online and in - person surveys with providers, and follow-up interviews. AMD WP 3 country teams coordinated research activities in their respective areas. Overall findings of this study are aimed at helping tool providers, national institutions, development planners, and potential investors better understand both the potential opportunities and challenges associated with the delivery of DCAS+ in each delta.